MODAL SOSIAL PENGURUS KARANG TARUNA DALAM MENANGANI KEMISKINAN DI DESA BUNISARI KECAMATAN WARUNGKONDANG KABUPATEN CIANJUR - Irma Dewi Istikomah; Raden Enkeu Agiati; Aries Effendi Ilyas (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
Social capital is an asset that is formed through social relations among people in order to achieve economic and social benefits. Social capital refers to the potential network, norms, and trustworthiness of community productivity. The purpose of this research is to explore about: 1) characteristics of the subject, 2) the subject's belief in dealing with poverty, 3) the norm embraced by the subject in dealing with poverty, and 4) the subject social network in dealing with poverty. The method used in this research is a qualitative method. The data source used is the primary and secondary data source. Data collection techniques use in-depth interviews, participatory observation, and documentation studies. The validity check of the data used is the validity of transferability, dependability, degrees of trust (credibility), and Confirmability with the technique of participation extension, persistence of observation, tiangulation, and peer inspection. The data analysis technique used is a qualitative data analysis technique. The results showed that the social capital of the cadets to deal with the problem of poverty needs to be strengthened, in the event that the trust has been strong, while for the norm and social network the management of coral Taruna is still weak due to the ignorance of the management of the coral Taruna about the importance of making a joint commitment to deal It is therefore offered the program